1999
DOI: 10.1001/archpsyc.56.6.557
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder in a Community-Based Twin Sample: Are There Different Genetic and Environmental Contributions for Men and Women?

Abstract: Background: Depression affects more women than men and often aggregates in families. Using a communitybased sample of twins, we examined the contributions of genetic and environmental factors to the risk of developing major depressive disorder and the effect of sex and different definitions of depression on the relative contributions of genetic and environmental effects. Sex differences in genetic effects were also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
132
6
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(158 citation statements)
references
References 29 publications
17
132
6
3
Order By: Relevance
“…It has been suggested that atopic disorders and depression share a common genetic etiology. 13 Since there is evidence that in women genetic factors play a greater role in the etiology of depression than in men, 58,59 we speculate that even the pathophysiology of the atopy-depression association could have arisen from different origins in females and males. For example, with respect to the serotonin metabolism, Enoch et al 60 have recently established that the 5-HT(2A) promoter polymorphism is associated with affective disorders in women but not in men.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that atopic disorders and depression share a common genetic etiology. 13 Since there is evidence that in women genetic factors play a greater role in the etiology of depression than in men, 58,59 we speculate that even the pathophysiology of the atopy-depression association could have arisen from different origins in females and males. For example, with respect to the serotonin metabolism, Enoch et al 60 have recently established that the 5-HT(2A) promoter polymorphism is associated with affective disorders in women but not in men.…”
Section: Discussionmentioning
confidence: 94%
“…The heritability of major depressive disorder is likely to be in the range of 31-42% [11]. Similarly, heritability based on twin studies is 40-50% [70][71][72][73][74][75] and adoption studies also support a role for genetic factors [76][77][78]. In comparison, the heritabilities of schizophrenia and bipolar disorder are estimated to be approximately 70% [11].…”
Section: Genetic Epidemiologymentioning
confidence: 99%
“…Although behavioural genetic studies generally report similar heritabilities for males and females, several authors report significantly higher heritability in females (see e.g. Bierut et al 12 and Kendler et al 13 ), a potentially interesting observation given the significantly higher prevalence of MDD in women. Also of note is the considerable familial comorbidity observed between MDD and other affective disorders, including anxiety and bipolar disorder, suggesting that these conditions may be aetiologically related and perhaps share common inherited risk factors.…”
mentioning
confidence: 97%